Cyberbully: cultural stereotypes among young adults / Muhammad Anwar Fahmi Hari Das Abdullah ... [ et al.] - Abdullah, Muhammad Anwar Fahmi Hari Das; Es Erwan Ezil, Syahira Natasha; Mohamad Jamal, Amani Alyaa; Mohd Nazri, Akmal Arief; Muhammad Aiman, Hana Aliyah; Ibrahim, Nur Alanna Khalish; Hassan, Mohd Sufiean (Faculty of Communication & Media Studies, 2022)
Cyberbullying is a hostile purposeful act committed by a group of individuals utilizing electronic forms of communication against a victim who is unable to defend themselves repeatedly and over time. Cyberbullying has been a widespread occurrence among teenagers and young adults. For some populations, it has become a major issue. The goal of this research is to find out how cyberbullying affects young adults. Apart from that, it investigates the link between stereotypical cyberbullying or bullying in general and the consequences it has on others, both domestically and abroad. The goal of this study is to look at different types of people and how bullying affects them in general. The participants in this study range in age from 13 to 30, although our primary focus is on youths. The result shows that cyberbullying can affect the victim's mental health. It can increase depressive affect, anxiety, loneliness, suicidal behavior, and somatic symptoms.